Hepatocellular carcinoma metastasis to the maxilla: a rare case. (24th July 2013) - Greenstein, A; Witherspoon, R; Iqbal, F; Coleman, H
Abstract: The manifestation of metastatic malignant disease in the oral cavity can present in a number of ways and may mimic benign conditions. This case reports a rare presentation from a metastasis of a hepatocellular carcinoma that had invaded the attached gingiva of the maxilla and which on initial inspection could have been misdiagnosed as a pyogenic granuloma. With the advent of new classes of drugs to manage this disease it could be expected that this presentation may become more common.